A User-oriented Protocol for Integrating Heterogeneous Communication Systems of Medical Facilities Using Ports - GierI, L.; Greiller, R.; Landersdorfer, Th.; Müller, H.; Überla, K. (Methods of Information in Medicine, 1989)
The crucial feature of future communication systems in hospitals will be the heterogeneity between the individual systems. People working in a hospital do not communicate via data objects, but via highly complex functions like preparation of a patient report or diagnosis of patients’ symptoms and signs. Essentially such tasks are accomplished by initiating remote functions in various modes of a communication system. The aim of the MEDAS protocol developed by our group is to propose a definition of such a high-level medical protocol and then to implement it. Our user-oriented protocol permits information exchange between heterogeneous systems. Modules and functions are defined. Message passing to and from a processor is realized using ports. The protocol sequence of every communication request is described. The relation of ports to the ISO model is specified. First experiences in a network for a medical school are reported.
Keywords: User-oriented Protocols; Distributed Systems; Communication; Message Passing Ports